2016
DOI: 10.1144/jmpaleo2015-022
|View full text |Cite
|
Sign up to set email alerts
|

New occurrences ofCyprideis torosa(Crustacea, Ostracoda) in Germany

Abstract: Living Cyprideis torosa (Jones, 1850) was found in Germany along the North Sea coast and on some islands, within the Baltic Sea and in coastal waters near the Baltic Sea, but also in some inland natural and anthropogenic saline waters. The natural inland waters were probably colonized by birds because this species was found only in permanent saline shallow lakes that provide resting places for migrating birds. Information on the fossil and Recent record and on the biology of C. torosa and its accompanying ostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
7
1
Order By: Relevance
“…However, it was later pointed out that such difference was probably related to changes in environmental conditions (e.g., salinity) (Van Morkhoven 1962; Keyser 2005; Frenzel et al 2012; Frogley and Whittaker 2016; Berndt et al 2019). Moreover, nding both forms from the same sites has already been reported in recent (e.g., Triebel 1941;Külköylüoğlu et al 1993Külköylüoğlu et al , 1995Scharf et al 2017; this study) and fossil forms (Nazik et al 2008;Witt 2010;Tuncer, pers. comm.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, it was later pointed out that such difference was probably related to changes in environmental conditions (e.g., salinity) (Van Morkhoven 1962; Keyser 2005; Frenzel et al 2012; Frogley and Whittaker 2016; Berndt et al 2019). Moreover, nding both forms from the same sites has already been reported in recent (e.g., Triebel 1941;Külköylüoğlu et al 1993Külköylüoğlu et al , 1995Scharf et al 2017; this study) and fossil forms (Nazik et al 2008;Witt 2010;Tuncer, pers. comm.…”
Section: Introductionsupporting
confidence: 85%
“…Also, live individuals of C. torosa have been recorded from streams (Külköylüoğlu et al 2020) and a lake (Lake Bafa) in Turkey (Akdemir et al 2020) where electrical conductivity values were below 400 µS/cm, referring to freshwater conditions. Cyprideis torosa was also reported from several other inland water types (e.g., springs, ditches, pit, ponds and brooks) in Germany where electrical conductivities ranged from 750 to 77400 µS/cm (Scharf et al 2017). Wouters (2017) clearly pointed out that species can be found from coastal zones of fresh, brackish, and marine habitats with high salinity values where the species was reported from 0.2 to 80‰ of salinity ranges in waters (e.g., see Bardawil inner lagoon) (Rosenfeld and Vesper 1977).…”
Section: Introductionmentioning
confidence: 66%
“…In modern environments, C. torosa prefers lagoons more than estuarine tidal flats and salt marshes, and thrives in oligo-to polyhaline waters, with muddy and sandymud sedimentation, avoiding active currents (Cabral et al 2017). This species tolerates low oxygen content, can be found at a water depth of up to 20 m (Scharf et al 2017) and is commonly found in waters that are Cl-SO 4 dominated and with an alkalinity/Ca ratio of <1 (Holmes & De Deckker 2017). If present, accompanying ostracod taxa such as Prolimnocythere sp.…”
Section: Paleoenvironmentsmentioning
confidence: 99%
“…focus on taxa occurring with torosa as important guides to salinity variations in the host milieu, given that torosa is usually monospecific only in hypersaline waters. Scharf, Herzog & Pint (2016) review the occurrence of torosa and associated taxa in German coastal waters and especially from natural and anthropogenic saline waters in central Germany.…”
Section: The Papersmentioning
confidence: 99%